Characterization of M Cells in Tear Duct-Associated Lymphoid Tissue of Mice: A Potential Role in Immunosurveillance on the Ocular Surface - Oya, Yuki; Kimura, Shunsuke; Nakamura, Yutaka; Ishihara, Narumi; Takano, Shunsuke; Morita, Ryo; Endo, Mayumi; Hase, Koji (Frontiers in Immunology, 2021)
The ocular mucosal tissues are exposed to potentially harmful foreign antigens in the air and tear fluid. The tear duct-associated lymphoid tissue (TALT) may contribute to immune surveillance in the eye region. Follicle-associated epithelium (FAE) of TALTs is classified as stratified squamous epithelium and consists of squamous epithelial cells arranged in layers on the basement membrane. In contrast, most mucosa-associated lymphoid tissue is covered by a monolayer of epithelium containing microfold (M) cells. Therefore, antigen uptake and the presence of M cells in TALT are not fully understood. In the present study, we found that a small population of FAE cells in the TALT expressed intestinal M-cell markers, namely Sox8, Tnfaip2, GP2, and OPG. This cell population was identified as functional M cells because of their uptake capacity of luminal nanoparticles. In addition, RANKL, which is essential for M-cell differentiation, was expressed by stroma-like cells at the subepithelial region, and its receptor RANK by the FAE in the TALT. The administration of RANKL markedly increased the number of Sox8+ M cells. In contrast, deficiency in OPG, which is an endogenous inhibitor of RANKL, increased the number of M cells in the TALT. These data demonstrate that the RANKL-RANK axis is essential for M-cell differentiation in the TALT. Furthermore, immunization via eye drops elicited the production of antigen-specific antibodies in tears, which was enhanced by RANKL administration. Thus, TALT M cells play an important role in the immunosurveillance of the eye region.